In vitro cultivation of Tamarindus indica L.: explants obtention and contamination in culture medium - Ferreira, Antonio Flávio Arruda; Monteiro, Laís Naiara Honorato; Rodrigues, Maria Gabriela Fontanetti; Oliveira, Natália Batista; Boliani, Aparecida Conceição (Comunicata Scientiae, 2018)
The tamarind tree (Tamarindus indica L.) is a common tree in tropical countries with a great exploitation potential due to its high nutritional value and important pharmaceutical characteristics, justifying its potential as a promising crop. The scarcity of scientific studies of the species, especially on propagation, hinders its availability and, consequently, the supply of the product in the market. The aim of this study was to verify the obtainment of nodal segments via sexual propagation and the in vitro establishment of sweet tamarind in MS culture medium (25, 50, 75 and 100% of salts) and with or without activated charcoal (2 g.L-1). The experiment was carried out in a completely randomized design in a 2 x 4 factorial scheme (presence and absence of activated carbon x salt concentrations), with 25 replicates, each replicate consisting of a test tube with an inoculated explant. According to the results, it is possible to conclude that from seedlings with 45 days after sowing, nodal segments of sweet tamarind are obtained for in vitro establishment. As a precursor of protocol for in vitro formation of healthy seedlings is indicated the use of MS culture medium with 75 % of the salts and added with 2 gL-1 of activated charcoal to reduce the contamination index.